Luminescent Defects in Single-Walled Carbon Nanotubes for Applications - Zaumseil, Jana (Advanced optical materials, 2022)
Semiconducting single-walled carbon nanotubes show extraordinary electronic and optical properties, such as high charge carrier mobilities and diameter-dependent near-infrared photoluminescence. The introduction of sp3 defects in the carbon lattice of these nanotubes creates new electronic states that result in even further red-shifted photoluminescence with longer lifetimes and higher photoluminescence yield. These luminescent defects or organic color centers can be tuned chemically by controlling the precise binding configuration and the electrostatic properties of the attached substituents. This review covers the basic photophysics of luminescent sp3 defects, synthetic methods for their controlled formation and discusses their application as near-infrared single-photon emitters at room temperature, in electroluminescent devices, as versatile optical sensors, and as fluorophores for bioimaging and potential super-resolution microscopy.